External Beam Accelerated Partial Breast Irradiation Yields Favorable Outcomes in Patients with Prior Breast Augmentation - Lei, Rachel Y.; Leonard, Charles E.; Howell, Kathryn T.; Henkenberns, Phyllis L.; Johnson, Timothy K.; Hobart, Tracy L.; Kercher, Jane M.; Widner, Jodi L.; Kaske, Terese; Barke, Lora D.; Carter, Dennis L. (Frontiers in Oncology, 2014)
Purpose: To report outcomes in breast cancer patients with prior breast augmentation treated with external beam accelerated partial breast irradiation (EB-APBI) utilizing intensity modulated radiotherapy (IMRT) or 3-dimensional conformal radiotherapy (3D-CRT), both with image-guided radiotherapy (IGRT). Methods and Materials: 16 stage 0/I breast cancer patients with previous elective bilateral augmentation were treated post-lumpectomy on institutional EB-APBI trials (01185132 and 01185145 on clinicaltrials.gov). Patients received 38.5 Gy in 10 fractions over 5 consecutive days. Breast/chest wall pain and cosmesis were rated by patient; cosmesis was additionally evaluated by physician per RTOG criteria. Results: The median follow-up from APBI completion was 18.0 months (range, 1.2-58.6). Little to no change in cosmesis or pain from baseline was reported. Cosmetic outcomes at last follow-up were judged by patients as excellent/good in 93.8% (15/16), and by physicians as excellent/good in 100% (16/16). Eight patients (50.0%) reported no breast/chest wall pain, and the remaining 8 patients (50.0%) reported mild pain. All patients remain disease free at last follow-up. The median ipsilateral breast, planning target volume (PTV), and implant volumes were 614 cc, 57 cc, and 333 cc. The median ratios of PTV/ipsilateral breast volume (implant excluded) and PTV/total volume (implant included) were 9% and 6%. Conclusions: These 16 breast cancer cases with prior bilateral breast augmentation treated with external beam APBI demonstrate favorable clinical outcomes. Further exploration of external beam APBI as a treatment option for this patient po